Performance management - an art and a science - Shellabear, Steve (Henry Stewart Talks, 2010)
Defining the ideal performance management system, The historical legacy of scientific management, Practical guidelines for set up, Managerial skills for implementation, Dispelling common misconceptions -Generating staff engagement -Summary of learning aims